Usefulness of balloon angioplasty for the right ventricle‐pulmonary artery shunt with the modified norwood procedure. Issue 5 (17th September 2012) - Ohno, Naoki; Ohtsuki, Shinichi; Kataoka, Koichi; Baba, Kenji; Okamoto, Yoshio; Kondo, Maiko; Sano, Shunji; Kasahara, Shingo; Honjo, Osami; Morishima, Tsuneo
<x xml:space="preserve">Abstract</x> Objective We sought to evaluate the efficacy of balloon angioplasty (BA) for severely desaturated patients due to a stenotic right ventricle (RV) to pulmonary artery (PA) shunt following modified Norwood procedure. Methods Of 87 patients who underwent a Norwood procedure with the RV‐PA shunt between February 1998 through March 2010, 22 (25%) patients underwent BA. The efficacy of BA was assessed by angiographic measurement of the changes in the internal diameters of the stenotic portions of the shunt, changes in arterial saturation and clinical outcomes. Results BA was performed for stenotic RV‐PA shunts following stage I palliation (n = 17, 77%), or those placed as an additional blood source (n = 5, 23%, 3 patients awaiting biventricular repair, 2 patients following stage II palliation). The location of the BA was at the distal anastomosis in 12 (54.5%), proximal anastomosis in 21 (95.4%) and in the mid‐portion of the shunt in 11 (50%) cases. The diameters of these three shunt portions were measured from the anterior–posterior and lateral angiographic images, increasing significantly after BA (p < 0.0001) in all. Arterial saturation significantly improved after BA in all cases (66.5 ± 4.3% to 79.4 ± 3.4%, p < 0.0001). Freedom from reintervention was 100%. All patients underwent subsequent elective planned surgery at an appropriate age with no mortality. Conclusions A BA‐alone strategy for a stenotic RV‐PA shunt was effective for all three shunt portions, minimizing shunt‐related premature surgical intervention. © 2012 Wiley Periodicals, Inc.